Explanation of the Importance of Trainer Instructions in Training Programs - Rahmat Rahmat; Andi Temmassonge; Muhamad Rohadi (Universitas Hamzanwadi, 2025)
Background Coaches play a crucial role in guiding athletes to reach their full potential through effective communication and instruction. The quality and clarity of coach instruction significantly impact athletes' understanding of the training program, their motivation, and overall performance outcomes. Objectives This study aimed to explore the importance of coach instruction in training programs and examine how instructional strategies contribute to athletes' achievement of training goals. This study also identified key factors influencing the effectiveness of coach instruction, including the ability to convey information clearly, provide individualized guidance, and enhance athlete motivation. Methods This study used a quantitative descriptive design by collecting and analyzing descriptive data. A total of 146 athletes participated in this study. Data were obtained using a questionnaire distributed through Google Forms. A quantitative descriptive method was used to identify factors influencing the effectiveness of coach instruction and to describe patterns and trends in the collected data. Results The findings showed that 62.5% of athletes agreed and 31.3% strongly agreed that the coach successfully delivered the training program, while 6.3% disagreed and none strongly disagreed. Similarly, regarding the coach's delivery of instructions, 62.5% agreed, 31.3% strongly agreed, 6.3% disagreed, and 0% strongly disagreed. However, when the coach gave very strict instructions, 37.5% agreed, 12.5% ​​strongly agreed, 43.8% disagreed, and 6.3% strongly disagreed, indicating mixed perceptions of an overly rigid coaching style. Research shows that clear and supportive coaching instructions have a positive impact on athlete performance and motivation. However, overly strict coaching instructions can reduce athlete effectiveness and satisfaction. Coaches must balance firmness and encouragement to optimize training outcomes.